Model for end-stage liver disease underestimates mortality of patients with acute-on-chronic liver failure waiting for liver transplantation. Issue 6 (June 2022) - Chang, Johannes; Matheja, Alexandra; Krzycki, Simon; Lutz, Philipp; Böhling, Nina; Glückert, Kathleen; Weismüller, Tobias J.; van Beekum, Cornelius; Manekeller, Steffen; Jansen, Christian; Kalff, Jörg C.; Strassburg, Christian P.; et al.
Abstract: Background and Aims: Patients with acute-on-chronic liver failure (ACLF) show excess mortality in MELD-Na based organ allocation for liver transplantation (LT). Whether MELD-based allocation in the Eurotransplant region similarly underprioritizes ACLF patients is unknown. Methods: 428 patients listed for LT from 01/2010 to 02/2021 at a tertiary center in Germany were screened and 209 patients included as derivation ( n = 123) and validation cohort ( n = 86). Competing risk analysis for waitlist mortality and LT as competing events was performed. Results: 90-day waitlist mortality for patients with MELD < and ≥ 25 at baseline was 9% vs. 33%, respectively ( p = 0.009). Competing risk analysis shows significantly higher 90-day waitlist mortality in patients listed with ACLF compared to those without ACLF ( p = 0.021) in the low MELD stratum. Probability of LT was similar between the two groups ( p = 0.91). In the high MELD group, 90-day waitlist mortality and rates of LT were not significantly different between patients with and without ACLF (31% vs. 20%, p = 0.55 and 59% vs. 60%, p = 0.72, respectively). Post-transplant survival was similar between patients with and without ACLF. This result was confirmed in the validation cohort. Conclusion: MELD-based organ allocation in the Eurotransplant region underestimates waitlist mortality in patients with ACLF in lower MELD ranges.